2013
DOI: 10.1089/thy.2012.0466
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of FOXE1 Expression in Papillary Thyroid Carcinoma by Immunohistochemistry

Abstract: FOXE1 overexpression and translocation to the cytoplasm are phenotypic hallmarks of tumor cells suggesting that FOXE1 is involved in the pathogenesis of PTC. Nuclear FOXE1 expression in tumor cells in the vicinity of the PTC border is associated with the presence of a risk allele of rs1867277 (c.-238G>A) in the 5' untranslated region of the FOXE1 gene, as well as with pathological characteristics of PTC, suggesting possible FOXE1 involvement in the facilitation of tumor development beginning at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…LD between rs965513 and rs1867277 is significantly weaker in populations of African or Asian ancestry [20], which is not surprising, since the LD block structure may be different in individuals of different ancestry [22]. In our study we observed LD between rs965513, rs1867277, and rs1443434; however, that between rs1867277 and rs1443434 was the strongest.…”
Section: Prace Oryginalnesupporting
confidence: 51%
“…LD between rs965513 and rs1867277 is significantly weaker in populations of African or Asian ancestry [20], which is not surprising, since the LD block structure may be different in individuals of different ancestry [22]. In our study we observed LD between rs965513, rs1867277, and rs1443434; however, that between rs1867277 and rs1443434 was the strongest.…”
Section: Prace Oryginalnesupporting
confidence: 51%
“…The relationship of FOXE1 to thyroid cancer may additionally be illustrated by immunohistochemical studies of FOXE1 expression in thyroid tumors (27)(28)(29). There has been a profound difference between staining patterns in different types of neoplastic tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of thyroid carcinoma, several studies have focused on relating FOXE1 expression and localization in cancer cells to tumor development. For instance, FOXE1 overexpression has been described in PTC (Nonaka et al 2008, Bychkov et al 2013, as well as a gradual decrease in its nuclear expression according to the degree of tumor dedifferentiation, along with cytoplasmic accumulation (Zhang et al 2006). This abnormal localization of FOXE1 could be related to thyroid tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%